Infants’ digestion at breast feeding (enzymological viewpoints) - G. F. Korot'ko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To characterize features of autolysis-induced digestion dynamics at breast feeding of infants.Key points. At child breast milk nutrients are hydrolysed in natural conditions by milk enzymes, secretions of digestive glands and secretory intestinal epithelial cells as autolytic-induced digestion with subsequent addition and advance of autologous digestion. Characteristic features of human milk enzyme activity during one-year lactation are adjusted to hydrolytic potential of infant’s digestive system.